Deciphering Modi’s Hindutva and Emerging Transnational Security Threats: The BJP’s Hindu Nationalism in The Light of Regional and Global Security Perspectives - Khan, Muhammad Farhan; Khalid, Iram; Jamshaid, Muhammad (Pakistan Languages and Humanities Review, 2024)
This paper examines the emerging trends of transnational security threats based on the ideological orientations of Hindutva. The major variables of the study revolve around the politico-religious beliefs of Rashtriya Swayamsevak Sangh (RSS) and Bharatya Janata Party (BJP) respectively. In addition, the researchers have also investigated the factors which collaborate to spread the toxic right wing Hindu religious fundamentalism abroad. There are multiple aspects intertwined with the transnational security threats which are deep rooted in, contemporary, Modi’s India. In recent decades, however, the status of India as a secular state is under threat due to rising preponderance of the Hindutva ideology through the entrenched rule of the Bharatya-Janata Party (BJP) and its Prime Minister, Narendra Modi. BJP as the political arm of the Rashtriya Swayamsevak Sangh (RSS), an organization dedicated to socially bifurcating India between a superior (according to themselves) Hindu class and inferior minorities, the party espouses Hindu nationalism, or Hindutva.